2018
DOI: 10.1039/c7cp07365h
|View full text |Cite
|
Sign up to set email alerts
|

Halocarbons as hydrogen bond acceptors: a spectroscopic study of haloethylbenzenes (PhCH2CH2X, X = F, Cl, Br) and their hydrate clusters

Abstract: The electronic spectra of 2-bromoethylbenzene and its chloro and fluoro analogues have been recorded by resonant two-photon ionisation (R2PI) spectroscopy. Anti and gauche conformers have been assigned by rotational band contour analysis and IR-UV ion depletion spectroscopy in the CH region. Hydrate clusters of the anti conformers have also been observed, allowing the role of halocarbons as hydrogen bond acceptors to be examined in this context. The donor OH stretch of water bound to chlorine is red-shifted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…Thus, Gw 1 must therefore have a structure like is not shifted quite as far as in the analogous 2-phenylethylalcohol cluster ("hydrate F", 3519 cm −1 ), 67 because the sulfur is a slightly weaker acceptor. The ν 3 red-shift is larger than is typically observed in single-donor systems 64,65 but is closer to the analogous PEAL cluster ("hydrate F", 3721 cm −1 ), 67 where water is receiving two weak H-bonds from neighboring aliphatic and aromatic CH groups. In PET, these CH•••O bonds are shorter by ca.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Thus, Gw 1 must therefore have a structure like is not shifted quite as far as in the analogous 2-phenylethylalcohol cluster ("hydrate F", 3519 cm −1 ), 67 because the sulfur is a slightly weaker acceptor. The ν 3 red-shift is larger than is typically observed in single-donor systems 64,65 but is closer to the analogous PEAL cluster ("hydrate F", 3721 cm −1 ), 67 where water is receiving two weak H-bonds from neighboring aliphatic and aromatic CH groups. In PET, these CH•••O bonds are shorter by ca.…”
Section: Resultssupporting
confidence: 60%
“…This produces one mode ( r C2H – r C3H , equivalent to 13 + 7b) that is blue-shifted and another mode ( r C5H – r C6H , or 13 – 7b) that is red-shifted. The predicted separation of 11 cm –1 overestimates the observed experimental splitting, although similar compositional changes have been observed in the anti and gauche conformers of substituted ethylbenzene derivatives benzenepropanenitrile, and haloethylbenzenes …”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…In contrast, the consideration of heavier halogens (that halogen bond: X=Cl, Br, I) has lagged. The few studies of heavy organohalogens as hydrogen bond acceptors have largely been theoretical, [9–11] with only a handful of experimental [12–18] and database [19, 20] studies reported. The importance of addressing this deficiency is underscored by the recent proliferation of halogen bonding materials, the ubiquity of the hydrogen bond, and a recent appreciation that hydrogen bonding can significantly influence halogen bonding (vide infra).…”
Section: Introductionmentioning
confidence: 99%
“…The R2PI setup used has been described previously. The specifics relating to this study are as follows. (S)-Nicotine purchased from Sigma-Aldrich was used as received.…”
Section: Experimental Methodsmentioning
confidence: 99%